New Observations on a Geological Hotspot Track: Excursions in Madeira and Porto Santo (1825) by Mrs T. Edward Bowdich. (30th June 2014) - Orr, Mary
Abstract This paper works with the modern concept of the geological hotspot track – the building processes and movements of volcanic island chains – applied strategically to one of its illustrative formations, the Madeira Archipelago. By analogy, however, the concept works equally well to describe the important early 19th‐century scientific knowledge‐building activity that produced Charles Lyell's On the Geology of Some Parts of Madeira (1854). A central section of the paper uncovers the contributions to knowledge of this geology before Lyell's, and in particular, Excursions of Madeira and Porto Santo (1825) by Mr [sic] T. Edward Bowdich. A thorough examination of this text then constitutes an important case study for literal and figurative investigation of geological hotspot tracks. The main argument proposed is that current specialist research forgets its submerged and longer histories to its detriment. Insights contained in older information often supply reminders of the key questions and contributions from the past that provide checks and balances for further developments of a field. By promoting multi‐level, multi‐stranded and multi‐lingual investigation of the history of 19th‐century geology in Madeira before Lyell (1854) as central to hotspot track research, this paper marks nodal conditions that constitute advancement in critical knowledge‐building within and outside the discipline of geology.